2022
DOI: 10.1007/s10664-022-10169-8
|View full text |Cite
|
Sign up to set email alerts
|

Small-Amp: Test amplification in a dynamically typed language

Abstract: Some test amplification tools extend a manually created test suite with additional test cases to increase the code coverage. The technique is effective, in the sense that it suggests strong and understandable test cases, generally adopted by software engineers. Unfortunately, the current state-of-the-art for test amplification heavily relies on program analysis techniques which benefit a lot from explicit type declarations present in statically typed languages. In dynamically typed languages, such type declara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Schoofs et al (2022) introduce PYAMPLIFIER a proof-of-concept tool for test amplification in Python. Recently, SMALL-AMP (Abdi et al 2022) demonstrated the use of dynamic type profiling as a substitute for type declarations in the Pharo Smalltalk language.…”
Section: Related Workmentioning
confidence: 99%
“…Schoofs et al (2022) introduce PYAMPLIFIER a proof-of-concept tool for test amplification in Python. Recently, SMALL-AMP (Abdi et al 2022) demonstrated the use of dynamic type profiling as a substitute for type declarations in the Pharo Smalltalk language.…”
Section: Related Workmentioning
confidence: 99%
“…Tools belonging to AMP add will generate new test methods based on the original handwritten test methods. The newly generated test methods try to improve the test suite based on metrics such as mutation score (e.g., DSpot and Small-Amp), 7,9 code coverage, [15][16][17] and reproduction of crashes (e.g., MuCrash). 18,19 AMP add is a special case of AMP change , as its tools and techniques only focus on the changed parts of the project under test compared to its previous version (e.g., DCI).…”
Section: Test Amplificationmentioning
confidence: 99%
“…Dynamic type profiling is introduced by Small‐Amp for test amplification in the dynamically typed language Pharo Smalltalk 9 by exploiting a Pharo‐specific reflectivity mechanism called Metalinks. However, the Metalinks implementation in Pharo takes advantage of the live nature of Pharo.…”
Section: Ampyfiermentioning
confidence: 99%
See 1 more Smart Citation
“…Exploiting this source of knowledge to improve software testing is called test amplification [3]. SMALL-AMP [4] is a test amplifier in Pharo that synthesizes new unit tests that increase the mutation coverage. SMALL-AMP is based on four main components: (1) a profiler which captures variables' type information, (2) an input amplifier which transforms existing test methods and generates new test inputs, (3) an assertion amplifier which regenerates the assertion statements, and (4) a selector that runs mutation testing and identifies the tests introducing new coverage.…”
Section: Introductionmentioning
confidence: 99%